PERFORMANCE ASSESSMENT SYSTEM NEEDS ANALYSIS OF LP3I BUSINESS COLLEGE LECTURER BANDA ACEH USING The METHOD Of VIEWPOINT ORIENTED REQUIREMENT DEFINITION (VORD) - Wibawa, Muhammad Bayu (Ubudiyah Indonesia University, 2016)
The needs of the software must be started from the parties involved in the development of a system to be built. The statement describes the needs of consumers or users of the system, nor the clien stokeholder though. In order to get the system needs to do some activity or activities include: requirement elicitation requirment, analysis and negotiation, requirement documentation, validation requirement. This activity aims to produce a document called document specification. Of some sort of method to analyze the needs of the system, one of the methods that can be applied on requirement engineering is the method of Viewpoint Oriented Requirements Definition (VORD). VORD method is one method used to define needs with an approach viewpoint (point of view) the users of the system. The results of the analysis of the VORD method this will generate requirement specification with the help of a tool i.e. VORD tool. The results of this analysis in the form of a document that describes the system needs to be built.Keywords: Requirement Engineering, VORD Method